Diabetes mellitus 2. typu a chronická obličková choroba - Ponťuch, Peter (Vnitrni lekarstvi, 2017)
The number of type 2 diabetic patients is increasing world-wide and a prediction of prevalence of chronic kidney disease up to 2025 in European diabetic population is alarming. Albuminuria and estimated glomerular filtration rate are cardinal biochemical parameters in diagnostics of diabetic nephropathy. Following diagnostic methods are also used: renal ultrasonography, ophthalmoscopy and in not clarified cases renal biopsy. Long-term optimal glycemic control, efficient antihypertensive treatment by angiotensin converting enzyme inhibitor, or angiotensin receptor blocker and recommended protein intake is a cornerstone of therapy. The research is presently focused on new pathophysiological mechanisms, as analysis of genome, microRNA, kidney injury biomarkers and proteomes.Key words: chronic kidney disease - type 2 diabetes mellitus.
Keywords: Biopsy; Angiotensin-Converting Enzyme Inhibitors; Humans; oftalmoskopie; Proteomics; MicroRNAs; Ophthalmoscopy; ledviny; Glomerular Filtration Rate; genomika; inhibitory ACE; Kidney; Albuminuria; Antihypertensive Agents; Ultrasonography; lidé; chronická renální insuficience; proteomika; hodnoty glomerulární filtrace; biopsie; Diabetes Mellitus, Type 2; albuminurie; ultrasonografie; diabetické nefropatie; Angiotensin Receptor Antagonists; Diabetic Nephropathies; mikro RNA; antihypertenziva; Genomics; Renal Insufficiency, Chronic; diabetes mellitus 2. typu; antagonisté receptorů pro angiotenzin